2020
DOI: 10.1111/epi.16547
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of using administrative healthcare data to identify epilepsy cases: A systematic review of validation studies

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
96
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(105 citation statements)
references
References 53 publications
9
96
0
Order By: Relevance
“…The validity of the operational definitions is another potential limitation. According to a recent systematic review, 27 administrative data can accurately identify people with epilepsy using operational definitions that combine disease codes with antiepileptic drugs (AEDs). In a previous Korean study using NHIS data, the positive predictive value for epilepsy identified using the criterion of one or more AED prescription with a diagnostic code representing epilepsy or seizure was 0.81 in 2009.…”
Section: Discussionmentioning
confidence: 99%
“…The validity of the operational definitions is another potential limitation. According to a recent systematic review, 27 administrative data can accurately identify people with epilepsy using operational definitions that combine disease codes with antiepileptic drugs (AEDs). In a previous Korean study using NHIS data, the positive predictive value for epilepsy identified using the criterion of one or more AED prescription with a diagnostic code representing epilepsy or seizure was 0.81 in 2009.…”
Section: Discussionmentioning
confidence: 99%
“…We believe the best way to avoid missing data or misclassifications is a manual chart review. Previous reports showed that combinations of ICD‐10 codes and ICD‐10 codes with other medical information (i.e., medication and procedure data) improved accuracy in identifying true diagnoses 30,36 . Since Japanese administrative claims data contain not only ICD‐10 codes but also a procedure code and drug information, 18,37,38 the algorithm of the combination of the ICD‐10 codes, procedure code and drug information may increase the accuracy of claims‐based diagnosis for predicting the gold standard based on actual manual medical chart review.…”
Section: Introductionmentioning
confidence: 99%
“…13 times the odds of readmission due to a psychiatric illness compared to those without epilepsy • Top psychiatric causes of readmission were mood disorders, schizophrenia and other psychotic disorders, and substance-related disorders • The results show that postpartum women with epilepsy are vulnerable to psychiatric illness requiring hospitalization International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) codes for epilepsy (345.0, 345.1, and 345.4-345.9), excluding isolated codes for status epilepticus (345.2, 345.3) without any epilepsy codes, in any diagnostic position at or before the time of delivery. 17,18 Women who had a diagnosis of epilepsy only after delivery were excluded. Women who delivered were identified using enhanced validated ICD-9-CM obstetric delivery diagnosis and procedure codes in any position (Table S1).…”
Section: Key Pointsmentioning
confidence: 99%